Studi Perbandingan Kurikulum Pendidikan Dasar Negara Federasi Rusia dan Indonesia - Alhamuddin Alhamuddin (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2017)
Abstract: This study aims to describe the curriculum development at elementary school in Russian and Indonesia. This study shows that there are many differences between both countries. Curriculum structure of the basic education in the Russian State has more hours per week than Indonesia's does, but in a year of study time in Russia is shorter than in Indonesia is. Assessment System in Russia learning outcomes serve as the basis of the information to determine the competence of which has been obtained by the learners, not as a measure for grouping students into groups. It is not much different in Indonesia. Keywords: Curriculum, Elementary School, Russian, Indonesia